PENGEMBANGAN MULTIMEDIA INTERAKTIF KARAKTERISTIK TATA SURYA (KATARYA) KELAS VI SEKOLAH DASAR - Naufal Daffa Atha; Wawan Priyanto; Husni Wakhyudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background that prompted this research was students' difficulties in following and understanding science lessons on the solar system. However, after further investigation through questionnaires, interviews, and needs analysis, the underlying problem was revealed to be a lack of teacher innovation in the learning process using instructional media. Teachers still use conventional learning techniques, focusing primarily on textbooks as learning resources. This leads to student boredom during the learning process The research questions are: 1) How does the development of interactive multimedia on the characteristics of the solar system (KATARYA) for sixth grade elementary school students based on Articulate Storyline work? 2) How is the feasibility of developing interactive multimedia on the characteristics of the solar system (KATARYA) for sixth grade elementary school students based on Articulate Storyline? 3) How is the practicality of developing interactive multimedia on the characteristics of the solar system (KATARYA) for sixth grade elementary school students based on Articulate Storyline? This research method is Research and Development (R&D). The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was used. Data collection techniques included observation, interviews, questionnaires, and documentation. Product testing was conducted at Muhammadiyah 16 Elementary School, Semarang. Based on the research conducted, the media validation score was 93%, categorized as "very valid," and the material validation score was 96%, categorized as "very valid." The questionnaire responses were then tested on 28 sixth-grade students. The calculated data showed that the questionnaire responses scored 95.7%, categorized as "very practical," while the teacher responses scored 100%, categorized as "very practical." These scores indicate that the KATARYA media is highly valid and practical for use in sixth-grade elementary school learning.